Chewing in temporomandibular disorder patients: an exploratory study of an association with some psychological variables - Brandini, Daniela A. [UNESP]; Benson, Janet; Nicholas, Michael K.; Murray, Greg M.; Peck, Christopher C. (Quintessence Publishing Co Inc, 2011)
Aims: To compare kinematic parameters (ie, amplitude, velocity, cycle frequency) of chewing and pain characteristics in a group of female myofascial temporomandibular disorder (TMD) patients with an age-matched control female group, and to study correlations between psychological variables and kinematic variables of chewing. Methods: Twenty-nine female participants were recruited. All participants were categorized according to the Research Diagnostic Criteria for TMD (RDC/TMD) into control (n = 14, mean age 28.9 years, SD 5.0 years) or TMD (n = 15, mean age 31.3 years, SD 10.7) groups. Jaw movements were recorded during free gum chewing and chewing standardized for timing. Patients completed the Depression, Anxiety, and Stress Scales (DASS-42), the Pain Catastrophizing Scale (PCS), the Fear of Pain Questionnaire-III (FPQ-III), and the Pain Self-Efficacy Questionnaire (PSEQ). Statistical analyses involved evaluation for group differences, and correlations between kinematic variables and psychological questionnaire scores (eg, depression, anxiety, stress) and pain intensity ratings. Results: Velocity and amplitude of standardized (but not free) chewing were significantly greater (P < .05) in the TMD group than the control group. There were significant (P < .05) positive correlations between pain intensity ratings and velocity and amplitude of standardized chewing but not free chewing. There were significant (P < .05) positive correlations between depression and jaw amplitude and stress and jaw velocity for standardized but not free chewing. Conclusion: This exploratory study has provided data suggesting that psychological factors, manifesting in depression and stress, play a role in influencing the association between pain and motor activity. J OROFAC PAIN 2011;25:56-67
Keywords: anxiety; clinical pain; depression; jaw movement; mastication; pain adaptation model; stress; temporomandibular disorders